Joint and several liability in EU Competition Law - Sadrak, Katarzyna (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
Contribution claims in antitrust are controversial and under-researched in the legal literature. This book provides the first comprehensive analysis of contribution claims in EU competition law. By drawing on the historical and current practice of EU and national courts, as well as national laws of major EU jurisdictions, it explains contribution claims in antitrust law in concrete and practical terms. It also provides much needed clarity on the relationship between competition law and joint and several liability, as well as guiding those concerned by contribution claims through the issues that are likely to arise. Topics examined include the requirements competition law sets for contribution claims; the criteria for dividing antitrust liability between individual co-infringers; the impact of EU Directive 2014/10; and whether liability sharing agreements can resolve the problems joint and several liability brings to EU competition law.
Introduction -- EU Competition Law and its impact on contribution claims -- Enforcing contribution claims under national laws -- Modifications of joint and several liability with respect to certain groups of entities -- Liability sharing agreements -- Conclusions and recommendations.
Title from publisher's bibliographic system (viewed on 20 Sep 2022).
Keywords: Antitrust law -- European Union countries; Correality and solidarity -- European Union countries